OS SERVIÇOS BANCÁRIOS NA PERSPECTIVA DO CLIENTE: UM ESTUDO EM UM BANCO ESTATAL DE SANTA ROSA - JASIOWKA, DIENY P. V.; KUHN, IVO N.; SOARES, JULIO C. V.; ZAMBERLAN, LUCIANO; FROEMMING, LURDES M. S. (Salão do Conhecimento, 2013)
Resumo